Study on HDPE Effect on Rutting Resistance of Binder - Benjamin Piromanski; Amin Chegenizadeh; Nuha Mashaan; Hamid Nikraz (Buildings, 2020)
Literature has shown positive results to using waste plastic as an alternative source for PMBs where considerable interest in using waste High-density polyethylene (HDPE) has been highlighted on improving rutting resistance. Most importantly, using a waste polymer for an application has benefits (i.e., maintenance, environmental) by improving the durability and quality of our roads and by avoiding polymers from landfill or incineration. This research uses the Multiple Stress Creep Recovery (MSCR) test to assess the performance of a binder modified with waste HDPE polymer. The outcomes of this research highlights that a HDPE content of 2–4% shows a substantial increase in rutting resistance and an improvement in elastic recovery. The elastic recovery reported does improve from previous research results however it does underperform in comparison with the Styrene butadiene styrene (SBS) polymer counterpart. Furthermore, it can be indicated by the aging index that a HDPE content of greater than 4% can be detrimental to the aging effects leading to fatigue cracking. It is recommended that a combination of both waste HDPE and an elastomeric polymer such as crumb rubber is to be used in future test work to improve the elastic recovery and address the effects of fatigue cracking.